The impact of psychospiritual program on state of depression, anxiety and stress among female juvenile delinquents - Muhammad, Hamizah; Rahim, Nurul Aisyah Awanis A; Sakari, Nor Shakirah Mohd; Johan, Sabihah; Arifin, Suhaili (International Journal of Public Health Science (IJPHS), 2024)
The participation of teenagers in inappropriate social actions is linked to the disregard for their mental health. This research was carried out to assess how a psychospiritual program impacts the reduction of depression, anxiety, and stress among delinquent adolescents. The study employed a quasi-experimental design, utilizing a single group for pretest-posttest evaluation. In this study, 36 delinquent adolescents who were females (N=36) and were enrolled in an Approved School in Terengganu, Malaysia, participated. The analysis was conducted through paired sample t-tests. The level of depression, anxiety, and stress before and after the psychospiritual program was assessed using the clinical scale for depression, anxiety, and stress (DASS-21). The results showed that the level of depression, anxiety and stress had decreased as much as 0.7619, 1.4643 and 0.7937 respectively after joining the program which was less than 0.05 (p=0.000 ≤0.05). This implies that the psychospiritual program exerts a significant influence in reducing depression, anxiety, and stress levels among adolescent delinquents. As a result, it is prudent to explore the psychospiritual approach as a potential alternative to the conventional allopathic intervention for addressing depression, anxiety, and stress problems especially among female delinquent adolescents at approved schools who have similar criterion.